1992
DOI: 10.1001/archsurg.1992.01420010115018
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin in the Management of Gastrointestinal Fistulas

Abstract: To evaluate the effectiveness of treatment with total parenteral nutrition (TPN) alone (group A) or combined with continuous intravenous infusion of somatostatin (group B) in postoperative gastrointestinal fistulas, a multicenter, controlled and prospective randomized trial was designed. We present the results obtained after the evaluation of 40 cases (group A, n = 20; group B, n = 20). No significant differences among these treatment schedules were observed in the percentage of closure of fistulas (group A, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 9 publications
0
55
1
2
Order By: Relevance
“…The literature confirms that they are associated with decreased output and a decreased time to closure in highly favorable fistulas that are most likely destined to close without surgery [2,11,42], but not necessarily increased non-operative closure rate [43][44][45][46]. Some studies document utility in higher output fistulas to help minimize fluid and electrolyte loss and protect the skin.…”
Section: Electrolytes and Nutritionmentioning
confidence: 88%
“…The literature confirms that they are associated with decreased output and a decreased time to closure in highly favorable fistulas that are most likely destined to close without surgery [2,11,42], but not necessarily increased non-operative closure rate [43][44][45][46]. Some studies document utility in higher output fistulas to help minimize fluid and electrolyte loss and protect the skin.…”
Section: Electrolytes and Nutritionmentioning
confidence: 88%
“…High dependency monitoring may or may not be necessary, but usually not in the absence of other complications. The value of octreotide in the treatment of established pancreatic fistulae is not clear with studies showing conflicting data [69, 70, 71, 72, 73]. Whilst there may be a limited role for octreotide in the management of pancreatic fistula, there may be more to be gained in the presence of an intestinal fistula (uncommon in pancreatic surgery).…”
Section: Fistulae Of the Pancreatointestinal Anastomosismentioning
confidence: 99%
“…A randomized open trial suggested that administration of somatostatin shortens the spontaneous closure time of postoperative pancreatic fistulas [53]. Another multicenter, prospective, randomized, placebo-controlled, double-blind trial found no influence on fistula closure time and clinical outcome with administration of early octreotide [54].…”
Section: Surgical Complications Following Pancreatic Resectionmentioning
confidence: 99%